ABUNDANCE OF WATER AND TRACE ELEMENTS IN THE ONGONITE MELT OF THE ARY-BULAK MASSIF, EASTERN TRANSBAIKAL REGION: EVIDENCE FROM STUDY OF MELT INCLUSIONS - Kuznetsov V.A.; Andreeva I.A.; Kovalenko V.I.; Antipin V.S.; Kononkova N.N. (My University, 2004)
The study of melt inclusions in quartz and topaz from ongonites of the Ary-Bulak Massif indicated their formation from the ongonite-type magmatic melt at 650-720°C. The parental magma was significantly enriched in H 2O (5-8.7 wt %), F (6-8 wt %), Li, Rb, Be, As, and W, but depleted in Sr, Ba, and Pb, thus indicating a high degree of differentiation.